2021
DOI: 10.1029/2020jg006213
|View full text |Cite
|
Sign up to set email alerts
|

Salt Marsh Light Use Efficiency is Driven by Environmental Gradients and Species‐Specific Physiology and Morphology

Abstract: Understanding ecosystem light use efficiency (LUE) of salt marshes, tidal wetlands with high salinity at the terrestrial-aquatic interface, is important to effectively estimate ecosystem productivity through remote sensing techniques. These salt marshes have high soil carbon burial rates, making them important ecosystems for studying blue carbon dynamics (Chmura et al., 2003;Mcleod et al., 2011). Juncus roemerianus and Spartina alterniflora are two dominate species found within salt marshes of the eastern Unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 111 publications
(198 reference statements)
1
14
0
Order By: Relevance
“…Our controlled in situ measurements of leaf-scale ChlF provide fundamental information that can explain vertical differences in the PSII working mechanism and how they may drive ChlF-SIF-GPP relationship observed at longer temporal scales. Our results, which showed a greatly reduced φPSII with the closure of PSII reaction centers and stomata during tidal flooding, offer further explanation for the results observed by Nahrawi et al (2020) and Hawman et al (2021). Their studies showed a significant decline in CO 2 assimilation rates and light use efficiency (LUE) in S. alterniflora during tidal flooding from a flux tower scale.…”
Section: Future Applicationssupporting
confidence: 85%
See 3 more Smart Citations
“…Our controlled in situ measurements of leaf-scale ChlF provide fundamental information that can explain vertical differences in the PSII working mechanism and how they may drive ChlF-SIF-GPP relationship observed at longer temporal scales. Our results, which showed a greatly reduced φPSII with the closure of PSII reaction centers and stomata during tidal flooding, offer further explanation for the results observed by Nahrawi et al (2020) and Hawman et al (2021). Their studies showed a significant decline in CO 2 assimilation rates and light use efficiency (LUE) in S. alterniflora during tidal flooding from a flux tower scale.…”
Section: Future Applicationssupporting
confidence: 85%
“…Hawman et al. (2021) further showed environmental factors, including air temperature, vapor pressure deficits, solar radiation, and tides affect LUE and GPP of S. alterniflora . All of those environmental variables could also be used in future studies to model and predict φPSII for marsh canopies so that φPSII predictions can be scaled to sites where in situ ChlF measurements are unavailable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Developed initially for terrestrial ecosystems, the EC technique is not yet widely applied in coastal wetland studies, where tidal and hydrological dynamics offer challenges (e.g. Barr et al, 2010;Forbrich and Giblin, 2015;Chu et al, 2021;Hawman et al, 2021;Hill et al, 2021). The knowledge gaps of CO 2 fluxes are particularly large for South America, where the great majority of EC studies are concentrated in the terrestrial ecosystems, with few studies performed in coastal wetlands (e.g.…”
Section: Introductionmentioning
confidence: 99%